(untitled) (Research, Society and Development, 2021)
This article is an excerpt from the research ’Philosophy textbooks in Brazil (1980-1990): a study on the origins and ways of teaching Philosophy’, carried out in the Master’s course of the Graduate Program in Education at the Federal University of Santa Maria. It aims to discuss the Philosophy textbooks produced in Brazil in the 1980s and 1990s. We problematize this Brazilian historical period, in order to understand the elements that have become conditions for textbooks, in general, and textbooks of philosophy, in particular, could emerge with strength and relevance in school philosophy teaching in Brazil. To this end, the study approaches a genealogical perspective by Michel Foucault (2015), as the writing of a story that refuses the perfection of the origins, recognizing the events as discursive plots, which intersect and intertwine in constant movements and forces that form and transform the context. It appears from the investigation that the emergence of the Philosophy textbook is conditioned by the forces at play that were plotted in the following periods: the end of the Military Dictatorship; the process of redemocratization (1980); the process of massification of teaching (1990); the struggles and struggles for the return of Philosophy teaching to high school / high school curricula and the publication of Law 9.349 of 1996.